P-139 St Oswald's hospice ambulatory care service – advance care planning, cross service working and preferred place of death. (19th November 2022) - Lever, Owen; Saunderson, Jen; Brown, Jo; Clark, Kath
Abstract : Background: It is known that many patients with haematological malignancies die in hospital (74.3%) (Howell, Wang, Roman, et al., 2017. BMJ Support Palliat Care. 7:150). Yet for those who discuss their preferred place of death, many would choose non-hospital settings (only 28.2% hospital). Those who never have the opportunity to discuss their preferred place of death are significantly more likely to die in hospital (Howell, Wang, Roman, Smith, et al., 2017). The ambulatory care service at St Oswald's Hospice has led to opportunities to engage patients in advance care planning discussions. We present Place of Death data, along with a case study to illustrate the importance of cross service MDT work. Method: A retrospective review of the notes of all patients who have attended the Ambulatory Care Service since its inception in March 2021. Data was captured on engagement in advance care planning, preferred place of death and actual place of death. Results: 32 patients attended the service (232 individual attendances). 23 were patients with a haematological malignancy. Nine had other diagnoses. 19 patients have engaged in advance care planning to date. 10 patients with haematological malignancies died during this period. Of the 10 patients who have died, preferred place of death was known for 7 (4 home, 1 nursing home, 2 hospice). The preferred place was achieved for all 7 patients. Of the three patients whose preferred place of death was not known, two had only attended the service once (4 and 6 months prior to death respectively) with a plan for advance care planning on future attendances. We also present a case study to demonstrate cross service working. Conclusion: The establishment of a service to provide planned blood product support and other treatments in a hospice setting has brought opportunities for patients to engage in advance care planning. This, along with close working with colleagues in community services, has led to achieving preferred place of death for a high proportion of patients.